2021
DOI: 10.3390/diagnostics11122386
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Value of Genetic Variants Associated with Anti-Social Behavior

Abstract: Insanity defense is sometimes invoked in criminal cases, and its demonstration is usually based on a multifactorial contribution of behavioural, clinical, and neurological elements. Neuroradiological evidence of structural alterations in cerebral areas that involve decision-making and moral reasoning is often accepted as a useful tool in these evaluations. On the other hand, the genetic predisposition to anti-social behavior is still controversial. In this paper, we describe two cases of violent crimes committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Additionally, MAO-A-L homozygous women with a history of childhood sexual abuse are more likely to show ASD symptoms. This interaction has only been reported in women who were sexually abused in childhood [10,14,15].…”
Section: Literature Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, MAO-A-L homozygous women with a history of childhood sexual abuse are more likely to show ASD symptoms. This interaction has only been reported in women who were sexually abused in childhood [10,14,15].…”
Section: Literature Studiesmentioning
confidence: 96%
“…revealed that he exhibited aggressive/violent antisocial behavior as well as non-violent antisocial behavior [11]. According to the most comprehensive studies on the MAO-A gene, the frequency of the 3R variant is estimated to be around 51-59% in African Americans and 33-37% in Caucasians [12][13][14]. On the other hand, the 4R allele is found in 36-43% of African Americans and 60-65% of Caucasians.…”
Section: Literature Studiesmentioning
confidence: 99%
“…Oliva and colleagues (2021) discuss two Italian criminal cases in detail in which defendants were carriers of genetic variants associated with antisocial behavior. They note that although scientific literature had demonstrated an association between the genetic variants carried by the two defendants and impaired impulse control, courts did not consider the information to be evidence of mental incapacity, as there was evidence of planning and deliberation in the commission of both violent crimes.…”
Section: Neurobiological Evidence In Criminal Courts Outside the Usmentioning
confidence: 99%
“…Children who witness violence – especially in case of recurrent episodes –tend to develop impaired attachment to primary caregivers and are exposed to significant physical, social and psychological issues like post-traumatic stress disorder and suicide ( 1 , 2 , 12 16 ). The particular vulnerability of the children is due to their scarce cognitive ability to distinguish between a threat to an adult and a threat to themselves ( 1 ).…”
Section: Introductionmentioning
confidence: 99%